Removal of phenol from wastewater using sawdust, polymerized sawdust and sawdust carbon - Jadhav, D N; Vanjara, A K (Indian journal of chemical technology, 2004)
The adsorption of phenol on sawdust, polymerized sawdust and sawdust carbon was investigated to assess the possible use of these adsorbents for the processing of phenolic wastewater. The influence of various factors such as initial concentration, agitation speed, and amount of adsorbent, temperature and pH on the adsorption capacity has been studied. The percentage removal of phenol is observed to increase, with the increase in initial concentration of phenol. With increase in temperature the adsorption of phenol decreases, indicating exothermic nature of the reaction. Adsorption isothermal data could be interpreted by the Langmuir and Freundlich equations. Kinetic data has been studied, using pseudo-second order equation for understanding the reaction mechanism. Thermodynamic parameters such as Delta G, Delta H and Delta S for the adsorption process were calculated.